USE OF COMPLEMENTARY HEALTH APPROACHES AND PRESCRIPTION OPIOIDS AMONG VETERANS WITH MUSCULOSKELETAL DISORDERS. (20th December 2022) - Han, Ling; Goulet, Joseph; Skanderson, Melissa; Redd, Doug; Brandt, Cynthia; Zeng, Qing
Abstract: Complementary and integrative health approaches (CIH) are recommended in national guidelines for managing chronic pain and de-prescribing opioids. We followed 1, 993, 455 opioid-naïve Veterans with musculoskeletal disorders for two years after index diagnosis during 2005-2017. CIH exposure was defined as primary care visits for acupuncture, massage and chiropractic therapy using natural language processing and administratively coded data. Opioid prescriptions dispensed during follow-up period were abstracted from Veterans Health Administration electronic pharmacy records. Propensity score (PS) was used to match one control for each CIH recipient. Overall, 140, 902 (7.1%) Veterans received CIH, with those age ≥65y the lowest prevalence (2.7%). Cox proportional hazard model revealed that time to first opioid prescriptions was longer for CIH recipients than PS-matched controls (136, 148 matched pairs) and varied across age (p for interaction 0.003). The adjusted Hazard Ratio (HR) was 0.48 (95% Confidence Interval (CI): 0.45-0.51) for Veterans age ≥65y, 0.44 (95% CI: 0.43-0.45) for 50-64y and 0.47 (95% CI: 0.46-0.48) for ≤49y. Restricted mean survival time (RMST) models estimated a smaller CIH benefit for Veterans ≥65y, with an average 3.3 (95% CI: 3.2-3.5) month RMST difference, in contrast to 4.2 (95% CI: 4.1-4.3) and 3.7 (95% CI: 3.6-3.8) months for younger counterparts. Sensitivity analyses in full cohort or modeling total supply and daily dose of opioid prescriptions derived consistent results. These findings suggest potential benefits of CIH in delaying and reducing opioids prescriptions for patients with chronic pain. The observations of lower rate and smaller benefit of CIH use among older Veterans warrants further investigations.